Failure analysis of waste heat boiler tubing caused by a high local heat flux. (June 2022) - Suwarno, Suwarno; Jabar I'jazurrohman, Abdul; Dwi Yudanto, Fajar; Djanali, Vivien S.
Highlights: The tubing of the waste heat boiler failed at the area of some distance from the gas inlet. The tube experienced excessive oxidation and wastage on the water-steam side. Computational modelling shows that there is high heat flux at the location of failure. The enlargement of the ferrule causes high heat flux to the steel tubing. Abstract: In a process gas synthesis for ammonia production, steam precursors are produced in a shell and tube heat exchanger (HE), called a waste heat boiler (WHB), because it uses heat from a gaseous produced in the reformer. The process gas flows in the tube, and a saturated water-steam mixture is on the outer shell side. In many cases, the waste heat boiler fails because of corrosion, erosion, and a combination of both. In this present work, a new failure mechanism of WHB tube is reported. The tube failed due to excessive oxidation wastage and had black products on the water-steam side. The oxide product was magnetite, intact on the surface, and the water-steam flow eroded some. The microstructure of the failed tube was composed of pearlite and ferrite without observed degradation. A computational model based on computational fluid dynamics revealed flow recirculation attributed to sudden enlargement at the end of the ferrule. This created high heat flux at some distance from the ferrule end; consequently, the tube excessively oxidized because of the high heat flux and temperature gradient across the tube thickness. This study provides a basis for developing HE designs and exploring the damage mechanism of shell and tube heat exchangers.